Larangan Tinggal Bersama Suami Istri Sebelum Walimatul ‘Ursy dalam Perspektif Hukum Islam: Antara Ketentuan Syariah dan Dominasi Adat - Nurul Azkia (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
The practice of prohibiting married couples from living together after the marriage contract but before the walimatul ‘ursy (commonly known as nikah gantung) remains socially binding in Hamayung Village, Hulu Sungai Selatan. This practice has generated controversy because it delays the exercise of spousal rights and obligations that, under Islamic law, should take effect immediately upon the conclusion of the marriage contract. As such, nikah gantung reflects a tension between the legal certainty of Islamic law and the dominance of customary norms as living law. This study aims to assess the compatibility of nikah gantung with Islamic legal principles through the frameworks of urf and maqasid al-shariah. The research adopts a normative Islamic legal (juridical-fiqhiyyah) method combined with a socio-legal approach, drawing on classical and contemporary fiqh literature, usul al-fiqh sources, statutory regulations, and limited field data to contextualize the practice. Data are analyzed qualitatively through takyif fiqhi, evaluation of urf, and maqasid-based assessment. The findings indicate that postponement of post-contractual rights may be permissible when it is voluntary and grounded in legitimate sharia-based reasons; however, the practice in Hamayung Village is collective, coercive, and reinforced by social sanctions, effectively transforming the recommended walimatul ‘ursy into a de facto legal condition. Consequently, this practice cannot be classified as urf sahih and contradicts legal certainty and family welfare. The study recommends strengthening legal awareness and repositioning customary norms to align with the objectives of Islamic law.